Correction: Tse et al. How COVID-19 Ceases All Older Adult Services & the Way Out for Community-Dwelling Older Adults with Chronic Pain. OBM Neurobiology 2023; 7: 183 - Mimi Mun Yee Tse; Shamay Sheung Mei Ng; Vivian Lou; Raymond SK Lo; Daphne Sze Ki Cheung; Paul H Lee; Shuk Kwan Tang; Siu Hang Leung; Percy Poo-See Tse (OBM Neurobiology, 2024)
CorrectionCorrection: Tse et al. How COVID-19 Ceases All Older Adult Services & the Way Out for Community-Dwelling Older Adults with Chronic Pain. OBM Neurobiology 2023; 7: 183Mimi Mun Yee Tse 1, *, Shamay Sheung Mei Ng 2, Vivian Lou 3, Raymond SK Lo 4, Daphne Sze Ki Cheung 5, Paul H Lee 6, Shuk Kwan Tang 7, Siu Hang Leung 1, Percy Poo-See Tse 1* Correspondence: Mimi Mun Yee Tse; E-Mail: mmytse@hkmu.edu.hkAcademic Editors: Ines Testoni, Adriano Zamperini and Lorenza PalazzoSpecial Issue: How COVID-19 Changed Individual and Social Life: Psychological and Mental illness Studies on the Pandemic OutcomesOBM Neurobiology2024, volume 8, issue 1doi:10.21926/obm.neurobiol.2401213Received: March 11, 2024Accepted: March 11, 2024Published: March 12, 2024The authors wish to make the following correction to the paper [1].